2009
DOI: 10.1097/pas.0b013e3181a92cbc
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Epithelioid Blue Nevus From Blue Nevus-like Cutaneous Melanoma Metastasis Using Fluorescence In Situ Hybridization

Abstract: Blue nevus (BN)-like cutaneous melanoma metastasis is a well-recognized variant of melanoma metastasis. These lesions may clinically and histologically simulate benign blue nevi. The histologic changes may be indistinguishable from conventional blue nevi or epithelioid blue nevi (EBN), a benign dermal-based melanocytic neoplasm with epithelioid morphology and heavily pigmented cytoplasm. Distinguishing BN-like cutaneous melanoma metastasis from benign conventional or EBN is important for staging and treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 10 publications
1
65
0
1
Order By: Relevance
“…21 It could also be useful if it really changes the treatment of patients, for example, with a thickness greater than 1 or 1.5 mm (according to the protocol), leading to interferon treatment or other adjuvant management such as sentinel node biopsy or adjuvant vaccine therapy. Other FISH applications have been reported to facilitate the differential diagnosis between (I) epithelioid blue nevus and cutaneous metastatic melanoma simulating blue nevus 22 or (ii) nevoid melanomas and mitotically active nevi, 23 (iii) conjunctival nevi from melanomas 24 or (iv) intranodal nevus from metastatic melanoma. 25 In conclusion, a single genetic test allowing the differential diagnosis between benign and malignant ambiguous melanocytic lesions does not yet exist.…”
Section: Discussionmentioning
confidence: 99%
“…21 It could also be useful if it really changes the treatment of patients, for example, with a thickness greater than 1 or 1.5 mm (according to the protocol), leading to interferon treatment or other adjuvant management such as sentinel node biopsy or adjuvant vaccine therapy. Other FISH applications have been reported to facilitate the differential diagnosis between (I) epithelioid blue nevus and cutaneous metastatic melanoma simulating blue nevus 22 or (ii) nevoid melanomas and mitotically active nevi, 23 (iii) conjunctival nevi from melanomas 24 or (iv) intranodal nevus from metastatic melanoma. 25 In conclusion, a single genetic test allowing the differential diagnosis between benign and malignant ambiguous melanocytic lesions does not yet exist.…”
Section: Discussionmentioning
confidence: 99%
“…16 The Abbott Molecular melanoma FISH test was also validated in critical differential diagnoses concerning histologically unequivocal benign and malignant blue nevi, nevoid melanoma, dysplastic nevi, desmoplastic melanoma, lentiginous melanoma, nevi with atypical epithelioid cell component, and Spitz nevi. [6][7][8][9][10][11][12]17,19 Obviously, a FISH test is not needed for histologically unequivocal cases. The only current justification for use of this expensive test in a diagnostic setting is to employ it as a diagnostic adjunct to help classify histologically ambiguous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several proof-of-principle studies showed potential applications of FISH to solve a variety of diagnostic dilemmas in the evaluation of melanocytic tumors, including differentiating blue nevus-like metastasis from blue nevus, mitotically active nevus from nevoid melanoma, and dysplastic nevus from superficial spreading melanoma. [7][8][9][10][11][12] Fluorescence in situ hybridization test abnormalities characteristic of melanoma were identified in lentiginous melanoma supporting this entity as a variant of melanoma.…”
mentioning
confidence: 99%
“…6 Numerous subsequent confirmatory 'proof of principle' studies validated the diagnostic utility of FISH in many different diagnostic settings, reporting a 75-100% sensitivity and 89-100% specificity of the assay in differentiating histologically unequivocal melanoma and nevi. 6,[9][10][11][12][13][14][15] However, most of the earliest proof of principle studies utilized histopathologically unambiguous nevi and melanomas to demonstrate the utility of FISH as an ancillary diagnostic test, yet FISH is predominantly deployed in the setting of morphologically ambiguous melanocytic tumors, where ancillary testing most usefully informs the diagnosis. The diagnostic utility of FISH is controversial in the setting of such ambiguous melanocytic lesions, where the overall reported sensitivity lies between 43 and 100% and the specificity between 33 and 83% using clinical behavior or expert histopathologic review as the gold standard.…”
mentioning
confidence: 99%